Design and fabrication of multi-patch elastic geodesic grid structures. (August 2021) - Pillwein, Stefan; Kübert, Johanna; Rist, Florian; Musialski, Przemyslaw
Highlights: Multi-patch elastic geodesic grids can be used to approximate complicated surfaces. Multi-patch elastic geodesic grids enable smooth coverage of curved surfaces. Multi-patch elastic geodesic grids can be deployed sequentially. Graphical abstract: Abstract: Elastic geodesic grids (EGG) are lightweight structures that can be deployed to approximate designer-provided free-form surfaces. Initially, the grids are perfectly flat, during deployment, a curved shape emerges, as grid elements bend and twist. Their layout is based on networks of geodesic curves and is found geometrically. Encoded in the planar grids is the intrinsic shape of the design surface. Such structures may serve purposes like free-form sub-structures, panels, sun and rain protectors, pavilions, etc. However, so far the EGG have only been investigated using a generic set of design surfaces and small-scale desktop models. Some limitations become apparent when considering more sophisticated design surfaces, like from free-form architecture. Due to characteristics like high local curvature or non-geodesic boundaries, they may be captured only poorly by a single EGG. We show how decomposing such surfaces into smaller patches serves as an effective strategy to tackle these problems. We furthermore show that elastic geodesic grids are in fact well suited for this approach. Finally, we present a showcase model of some meters in size and discuss practical aspects concerning fabrication, size, and easy deployment.